Effect of hexadecyltrimethylammonium bromide-based microemulsions on the rate of decomposition of the beta-lactam antibiotic cephaclor - Oliveira, Anselmo Gomes de [UNESP]; Scarpa, Maria Virgínia; Chaimovich, Hernan (Amer Pharmaceutical Assn, 1997)
Microemulsions of hexadecyltrimethylammonium bromide (HTAB)/n-butanol/hexadecane/water catalyze the intramolecular degradation of cephaclor. The rate increase is a sensitive function of the microemulsion volume fraction and salt concentration. The effects of microemulsions, analyzed quantitatively using a pseudophase ion-exchange model, assumed that the extent of ion dissociation from the microemulsions varies with volume fraction. Comparison of micellar and microemulsion effects on the same reaction shows that microemulsions are less effective catalysts. Acceleration decreased significantly by increasing the relative proportion of n-butanol ratio in microemulsions and by addition of n-butanol in HTAB micelles. Comparison of the activation parameters of the reaction in aqueous solution, microemulsions, and micelles suggests that catalysis by both aggregates is driven mainly by entropic contributions.
Keywords: Butanol; Cefaclor; Cetrimide; Hexadecane; Dissociation; Drug decomposition; Drug degradation; Drug solubility; Entropy; Ion exchange; Microemulsion; Molecular dynamics; Catalysis; Cefaclor; Cephalosporins; Cetrimonium Compounds; Emulsions; Kinetics; Thermodynamics